The Relationship Between Education Level And Mother's Behavior In Female Circumcision - Surlina, Surlina; Maritalia, Dewi; Agustina, Agustina (Jurnal Maternitas Kebidanan, 2025)
Female circumcision is still common in Indonesian society even though it has no medical basis and endangers women's reproductive health. One factor thought to influence this practice is the mother's level of education. Determine the relationship between a mother's education level and her behavior in performing female circumcision. This was an analytic study with a cross-sectional design. The study population consisted of all mothers with daughters aged 2-5 years in the Peusangan Health Center service area of Bireuen Regency. A total of 105 mothers were surveyed. Random sampling was used for the sample selection, and the chi-square test was used for the data analysis with a significance level of 95% (α = 0.05). Most respondents (91.4%) had a formal education, and 66.7% of respondents performed circumcision on girls. There is a significant relationship between the mother's level of education and circumcision behavior (p = 0.028). Maternal education level significantly influences female circumcision behavior. Increasing community education, especially among mothers, about the negative impacts of female circumcision is necessary to support the elimination of this practice